The Kautz Gyula College of Economics in the 2000s - Farkas, Péter; Koppány, Krisztián (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
In addition to teaching, active scientific research is a central element of university life. Accordingly, one of the important criteria for the transition from college to university was the promotion of research. This meant more emphasis on publication activity than before, which created new opportunities for students as well as university researchers.The Scientific Student Circle (TDK) already had a long tradition before the university was established, and the creation of the professional colleges gave this process a further boost.The first professional college of Széchenyi István University, the predecessor of the Kautz Gyula Professional College of Economics (KGYKSZ), the Győri Széchenyi Professional College (GySzSz), was founded in 1997 by Zoltán Ferenczi, associate professor and then head of the Department of Statistics, whose goal was to find and support students with outstanding abilities and a desire to achieve. In the summer of 1997, he sent letters to the business students with the best academic results. These students became the founding members of GySzSz.The significance of the specialist college movement, which began in the Faculty of Economics and flourished in the 2000s, is well illustrated by the fact that later, following the specialist college, the Faculty itself took the name of Gyula Kautz, an economist, statistician, central banker and statesman who was born and raised in Győr.